Improvement of rodent pest control strategy: I - Selection of an adequate preservative for bait base longevity under unfavourable environmental conditions - Blažić, Tanja; Đurović-Pejčev, Rada; Đorđević, Tijana; Jovičić, Ivana; Međo, Irena; Stojnić, Bojan; Jokić, Goran (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2024)
Preservation of the appearance, structure and most importantly the attractiveness of baits targeting harmful rodents over extended periods of their exposure is one of the main tasks in the process of bait formulation. The impact of several preservatives, different methods of homogenization of main bait components, and base-paraffin ratios on the extension of longevity of bait base was examined under controlled laboratory conditions. Baits based on ground maize grain were exposed to unfavourable environmental conditions, such as high temperature (30 °C-35 °C) and air humidity (90%-95%). The exposure period was 9 days, and potential mold development was monitored over the same period of time. Sodium benzoate was found deficient in providing a satisfactory effect on bait longevity (<5 days), in contrast to potassium sorbate (>7 days) and sorbic acid, which provided the longest extension in bait sustainability (>9 days). Preservative application can significantly extend bait longevity under unfavourable environmental conditions. Extended bait functionality is important for rodent pest control procedures in habitats where unfavourable environmental conditions prevail, such as sewers and water supply grids (collectors and pumping stations), public areas, housing facilities (boiler rooms, moist sellers, etc.).